Immobilization of ZnO nanoparticles on fluorinated perlite granules for the photocatalytic degradation of methylene blue - Nguyet Anh Pham; Thi Huynh Nhu Nguyen; Tuan Ngoc Tran; Quy Tu Nguyen; Tien Khoa Le (Vietnam Journal of Science, Technology and Engineering, 2017)
The fluorination of perlite granules and the immobilization of ZnO nanoparticles on the perlite surface were carried out at the same time by a simple impregnation method to create new highly photocatalytic materials which are easily separated from reaction solutions after treatment. The influence of perlite fluorination on the crystal structure, morphology, UVvisible absorption, and surface functional groups of ZnO, as well as on the ZnO content on perlite, was respectively characterized by XRD, FE-SEM, UV-Visible diffuse reflectance, FTIR and atomic absorption spectrometry. The photocatalytic activity was evaluated via the extent of degradation of methylene blue under UVA irradiation. According to the results, the fluorination of perlite leads to numerous effects on ZnO, such as the decline of ZnO cell parameters, the increase of ZnO content on perlite granules (resulting in the enhancement of light absorption in UVA range), and the decrease of ZnO particle size, which can effectively improve its photocatalytic performance. The photocatalysts were also found to be able to stay afloat on water, allowing for easy separation from the reaction solution.